Clean C++20 : sustainable software development patterns and best practices - Roth, Stephan, 1968- (Apress, 2021)
Write maintainable, extensible, and durable software with modern C++. This book, updated for the recently released C++20 standard, is a must for every developer, software architect, or team leader who is interested in well-crafted C++ code, and thus also wants to save development costs. If you want to teach yourself about writing better C++ code, Clean C++20 is exactly what you need. It is written for C++ developers of all skill levels and shows by example how to write understandable, flexible, maintainable, and efficient C++ code. Even if you are a seasoned C++ developer, there are nuggets and data points in this book that you will find useful in your work. If you don't take care with your codebase, you can produce a large, messy, and unmaintainable beast in any programming language. However, C++ projects in particular are prone to get messy and tend to slip into a maintenance nightmare. There is lots of C++ code out there that looks as if it was written in the 1980s, completely ignoring principles and practices of well-written and modern C++. It seems that C++ developers have been forgotten by those who preach Software Craftsmanship and Clean Code principles. The web is full of C++ code examples that may be very fast and highly optimized, but whose developers have completely ignored elementary principles of good design and well-written code. This book will explain how to avoid this and how to get the most out of your C++ code. You'll find your coding becomes more efficient and, importantly, more fun. You will: Gain sound principles and rules for clean coding in C++ Carry out test-driven development (TDD) Better modularize your C++ code base Discover and apply C++ design patterns and idioms Write C++ code in both object-oriented and functional programming styles.